(untitled) (Journal of Dhaka Medical College, 2011)
Context: A randomized prospective study was done to see the effect of therapy with cyclosporine and prednisolone in patients with idiopathic aplastic anemia. Methods: A total of 40 patients were included in this study .We use cyclosporine 6mg/kg/ day and prednisolone 30 mg /day for a period 6 months. The study was done during the period of July 2005 to October 2006. In the study population, out of 40 patients, 26 were male and 14 were female. 2 patients died early in the treatment and 4 patients transformed into acute leukemia. The rest 34 patients completed therapy for 6 months. Results: Among the 34 patients, 22 patients responded to therapy and 12 patients were nonresponders. According to severity, population distribution was as follows: 12 (35.30%) patients were non-severe AA, 19 (55.88%) patients were severe AA and 3 (8.82%) patients were very severe AA. Out of 22 patients (responders), 7 (31.82%) patients start to respond at 3rd month, 5 (22.73%) patients at 4th month, 8 (36.36%) patients at 5th month and 2 (9.09%) patients were very late to respond; they respond at 6th month. At the end of 6th month trial, 7 (20.59%) patients had complete response, 15 (44.12 %) patients had partial response and 12 (35. 29%) patients were non-responders; overall response rate was 64.71%. The adverse effects of the therapy were found e.g. weight gain in 100%, hypertension in 26.47%, increased serum creatinine in 38.23%, hyperglycemia in 20.58% and infection due to immunosuppression in 14.71%. Conclusion: Combination of cyclosporine and prednisolone therapy merits further study as primary treatment for aplastic anemia in patients who are not able to undergo bone marrow transplantation. Key words: Aplastic anaemia; immunosuppressive therapy; combination of cyclosporine and prednisolone. DOI: 10.3329/jdmc.v19i2.7074 J Dhaka Med Coll. 2010; 19(2) : 80-85